Research on Settlement and Deformation Control of Newly-built High-speed Railway and Existing Line Foundation under Different Overlap and Filling Types - Li Wen-yi; Jin Chao-qi; Zhu Jun-hua; Guo Hao-sen; Luo Wen-jun; Chen Li (E3S Web of Conferences, 2021)
Subgrade filling of high-speed railway will cause additional settlement and deformation of existing lines.In this paper,using the finite element analysis platform (Taxis 2D) and considering the settlement of the existing line itself, This paper analyzes the impact of the new and old subgrade lap type and the layer filled this lesson of the new subgrade on the implementation of the existing subgrade. The results illustrate the following points:(1) Compared with different overlapping surface types, different filling those points have a greater impact on the settlement of the existing line; (2) The height of the steps is 0.6m and the width is 1.0m.In the subsequent layered filling construction process, each level The loading capacity of 30cm is more reasonable, which can effectively control the influence of the existing line on the additional settlement of the existing railway. The research results can provide a reference for the optimization of similar roadbed width construction.